On the Oral Health and Chewing Enjoyment of the Elderly: A Review from the Point of Mechanics. Issue 4 (12th July 2016) - Xu, Xianzhong
Abstract: With the advent of an aging society, the biggest challenge for the study of food science and technology is how to provide the best diet for older people with reduced chewing ability. General health is usually associated with oral health and healthy ageing is affected by what humans eat. Foods for the elderly should give them the maximum masticatory pleasure while satisfying their nutritional needs. It is well known that food oral processing is not only dominated by oral cavity structure and physiological state of human body, but also affected by the mechanical processes of food destruction in the mouth. Perception of food texture is thought to be the cognition of the human brain to the information of food deformation and fracture during oral processing. Increasing chewing difficulty due to the impaired dental functions is an major problem affecting the ability of food intake for many older people. From the viewpoint of mechanics, the manner of the deformation or breaking of an object is strongly dominated by its mechanical and geometrical properties of the materials and the conditions in which the object is loaded. It is therefore suggested that the food destruction process in the mouth might be investigated using the methods established in the engineering field. In this review, the main factors that affecting chewing behaviors of the elderly are analysed and discussed. The possibility of applying fracture mechanics theory and material structural optimization techniques to the design and production of food structures for older people is proposed. Practical Applications: Population aging means that the food industry is required to provide best diet for older consumers who may encounter chewing difficulty and dysphagia problems. People with deficient oral strategy need foods not only having easy‐to‐chew/swallow feature, but also can satisfy their chewing pleasure. Food structure design is a new direction of food science for the development of food products. The fundamental issue is to have a proper understanding how designed food is formed and fractured in the mouth. This work analyses the main factors that influence the chewing behaviors of the elderly and introduces fracture mechanics theory into the field of food oral processing. It will provide a new view‐angle to understand both the food destruction process and the texture perception mechanism in the mouth.